Strategi Dinas Kependudukan Dan Catatan Sipil Dalam Memberikan Pelayanan Khusus Disabilitas Kota Pekanbaru - Riyan Aszaky Hendrika; Harapan Tua (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to find out the strategies and obstacles factors of the Department of Population and Civil Registry in providing special services for disabilities in Pekanbaru City. This study uses a type of qualitative research. The data needed both primary data and secondary data obtained through observation, interviews and documentation are then analyzed based on the research problem. The results of the study show the strategy of the Pekanbaru City Population and Civil Registry Office in providing special services for disabilities, namely optimizing the role of human resources and optimizing facilities and infrastructure to meet the needs of persons with disabilities, for example issuing service innovations, especially online services with the SIPINTAR PEDULI program. Improving coordination and cooperation with related SKPD/Institutions such as SLB, Social Institutions, and Correctional Institutions. Increasing public awareness by socializing so that people know the importance of population administration documents, especially KTPs for persons with disabilities. Factors inhibiting the strategy include limited equipment, internet network and behavior of people with disabilities. Keywords: Strategy, Service, Disability